A formação continuada do professor de Educação Infantil numa perspectiva da autoria por meio de ateliês biográficos - Santos, Alessandra Olivieri (2018)
This study aimed to provide a reflexive exercise to the Children Education teacher about her professional role as protagonist of the teaching action, pointing to the continuing formation and the guiding principles’ elaboration which may contribute to the education project of teachers in a Children Education Centre (CEC) from the Municipal Education System of São Paulo, located in the South end of the city. The research presented the following problematization: How the Pedagogical Coordinator may give a continuing formation to this teacher that allows her professional development and transform her pedagogical practices. In order to develop this work, a quantitative approach was used with the purpose of giving a new meaning for the work context and the educating space of six teachers, research subjects, aiming to understand their visions and world conceptions, their ways of acting and thinking through the life histories recalled in seven meetings of biographical workshops. The procedures used to produce the data were the questionnaire and life narratives based on the theories of Josso (2004) and Delory- Momberger (2006) and defined as a formative approach focused on the learning subject. In order to discuss the professional development, the research was supported by the theoretical assumptions of Imbernón (2011) who highlight the importance of thinking about the formation and the journey of the teaching professionalism. The life histories provided, to the teachers’ group, the building of a collaborative network of memories and meanings for the profession valorization and understanding, allowing to give a new meaning the space of continuous formation that the School should be. The teachers rebuilt their steps and thought about a formation and a voice of a professional group which fell itself invisible in front of the Education System. From the analysis, this study proposed guiding principles for a formation project which meet the individual needs of teachers, respecting the collective space in the Scholar Unity, enforcing the educational legislation and, mainly, contributing to changes in the pedagogical practices of teachers and to improve the teaching and learning process with babies and children in the Children Education